2011
DOI: 10.4314/sajas.v41i1.66044
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of the prolactin gene and its association with egg production traits in native Chinese ducks

Abstract: As a candidate gene related to egg production, prolactin plays a crucial role in the reproduction of birds. In this study, polymorphism of the prolactin gene was screened in six Chinese native duck breeds (Shanma, Shaoxing, Youma, Jinyun, Jingjiang and the F 2 resource population of white Liancheng X white Kaiya) using PCR-SSCP and direct sequencing. The results showed that 12 SNPs were detected: C-213T in the 5 flanking region, A-1842G in exon 2, A-3869G in exon 4 and C-5961T in exon 5, T-295C, C-381A and A-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
3
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(65 citation statements)
references
References 16 publications
3
56
3
3
Order By: Relevance
“…The expressed product of this gene is the prolactin hormone, which is a multifunctional protein hormone involved in the control of a wide variety of physiological processes in vertebrates, including osmoregulation, reproduction, immune responses (Clapp et al 1994), water and electrolyte balance, endocrinology (Bole-Feysot et al 1998). In avian species, prolactin is a crucial hormone in induction and maintenance of incubation behaviour and regulation of the follicular development (Wang et al 2011). Furthermore, it has been observed that the prolactin hormone is involved in the formation of the egg (Hazelwood 1983).…”
Section: Introductionmentioning
confidence: 99%
“…The expressed product of this gene is the prolactin hormone, which is a multifunctional protein hormone involved in the control of a wide variety of physiological processes in vertebrates, including osmoregulation, reproduction, immune responses (Clapp et al 1994), water and electrolyte balance, endocrinology (Bole-Feysot et al 1998). In avian species, prolactin is a crucial hormone in induction and maintenance of incubation behaviour and regulation of the follicular development (Wang et al 2011). Furthermore, it has been observed that the prolactin hormone is involved in the formation of the egg (Hazelwood 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Some research reported that polymorphism analysis of mtDNA marker included ND1-6, ND4L, COX 1-3, ATP6 and ATP8 in Beijing duck in China (C. Zhang et al, 2010), prolactin gene polymorphism in purebred China duck (Shanma, Shaoxing, Youma, Jinyun, Jinjiang and interbred (F2) of white Liancheng and white Kaiya) (Wang et al, 2011) (Hao, 2009) can be done by using PCR-SSCP (Single Stranded Conformation Polymorphism) and the DNA sequencing products. The restriction profiles correspond to Wolf et al (2000).…”
Section: Resultsmentioning
confidence: 99%
“…Perbedaan sifat kuantitatif ini disebabkan oleh faktor genetik dan faktor lingkungan yang berupa manajemen pemeliharaan yang berbeda (Martojo, 1990 (Nenzhu et al, 2009;Wang et al, 2011;Wang et al, 2012).…”
Section: Hasil Dan Pembahasanunclassified